“Rodovírus” ou “Caronavírus”? Mapas da Distribuição do Covid-19 na Região Sul do Brasil: Indícios da contaminação por rodovias - Ricardo R. Monteiro; Rangel Angelotti; Luiz Fernando de Carli Lautert; Paulo Eduardo Angelin; João Portes (Confins)
Covid-19 is an infectious disease caused by a coronavirus. In Brazil, the first cases arrived via the airports of the city of São Paulo and spread throughout the country. In this paper maps of the Southern region allow the visualization of COVID-19 cases by municipality, cumulative cases, cumulative deaths, incidence rate of cases per 100,000 inhabitants (relationship between cases and population of the municipality) and the case-fatality rate (relationship between the number of deaths and the number of people infected). The maps indicate that the highest concentrations occur on a few sections of the road network, mainly along the BR-386 motorway, which connects Carazinho - RS to Porto Alegre - RS, of the Freeway motorway, which connects the capital from the State to the beaches, and BR-101, one of the most important of the north-south link. Although not conclusive, the diagrams presented can be used to plan emergency actions for the disease.